Improved Positioning Control Of A Rotary Switched Reluctance Actuator Using Modified PID Controller - Tee,, Siau Ping (2019)
Over the past decade, the rotary switched reluctance actuator (SRA) has been gaining attention not only in the areas of industrial applications as well in promising research areas such as robotics and automotive engineering. The popularity can be much associated with the attractive advantages SRA has to offer such as inherent fault tolerance, simple and robust structure in addition to the ability for high frequency operations. Despite the attractive advantages it has to offer, SRA exhibits significant nonlinear characteristics due to its unpredictable magnetic flux flow and operation in saturation region. Subsequently, these dynamic behaviors often make modelling and real time motion control a challenging effort. Although various control methods have been developed, these controller design procedures frequently require exact model of mechanism and deep understanding in modern control theory which leads to their impracticability. Henceforth, in this research, a practical control strategy namely the modified proportional-integral-derivative (PID) control scheme is proposed for point-to-point motion control of the rotary SRA mechanism. The practical control scheme presented heavily emphasizes on simple structure and straightforward design framework. Hence, the proposed modified PID controller includes control elements that are derived from the measured open loop responses. Complex system modelling or high computational learning algorithms are not required in the controller design process. The performance evaluation is examined and compared to a conventional PID controller through experimental works. At fully aligned and almost aligned positions, experimental results showed that the proposed controller successfully reduced steady-state error in step positioning by an average improvement of 94%. The maximum overshoot and settling time are improved by an average 62.5% and 47%. At intermediate positions, although zero steady- state error can be enjoyed on both controllers, modified PID controller performed better by showing a reduced overshoot and settling time response of 60% and 37% improvement. Overall, the proposed controller displayed superiority compared to conventional PID controller with a smoother displacement response with reduced steady-state error, overshoot and settling time in all positioning tasks.